2011
DOI: 10.1117/12.884920
|View full text |Cite
|
Sign up to set email alerts
|

A novel FBG-based fence with high sensitivity and low nuisance alarm rate

Abstract: A quasi-distributed FBG-based fiber-optic fence is investigated in this paper. A novel intrusion detection method is proposed based on the autocorrelation characteristics of the signal with and without disturbances, which is very effective to detect extremely weak signals even from nonequivalent sensor nodes in a large sensor network. When analyzing the intrusion signal's characteristics and excluding the false alarm sources, such as environmental interferences and others, Nuisance Alarm Rate (NAR) is well con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…From 2011-2013, Wu et al [87]- [91] from the same group reported a FBG based intrusion detection fence system. They reported the progress of their quasi-distributed FBG system by analyzing a number of different algorithms to improve the POD and reduce the NAR.…”
Section: B Fully Distributed Fiber Optic Pidsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2011-2013, Wu et al [87]- [91] from the same group reported a FBG based intrusion detection fence system. They reported the progress of their quasi-distributed FBG system by analyzing a number of different algorithms to improve the POD and reduce the NAR.…”
Section: B Fully Distributed Fiber Optic Pidsmentioning
confidence: 99%
“…They reported the progress of their quasi-distributed FBG system by analyzing a number of different algorithms to improve the POD and reduce the NAR. These methods include; autocorrelation characteristics analysis, where the proposed system has a predicted POD of 99.5% and a NAR of 0.5% [87], principle component analysis, which results in a recognition rate of 96.52% for eight type of intrusion methods [88], and 3-layer back-propagation artificial neural network, which has a recognition rate of 96.03% [90]. In addition, they stated their system could predict fire threats without any additional components [89].…”
Section: B Fully Distributed Fiber Optic Pidsmentioning
confidence: 99%
“…Wu et al [74] described a sensor capable of measuring temperature and hydrostatic pressure simultaneously using a FBG in a standard section of fiber combined with a FBG in a section of grapefruit microstructured fiber. The FBGs showed a similar response to changes in temperature of approximately 11 pm/ • C. However, the microstructered FBG was significantly more sensitive to pressure variations having a sensitivity of 13.4 pm/MPa, compared to 4 pm/MPa for the standard FBG.…”
Section: Fbg Pressure Sensorsmentioning
confidence: 99%